Alasan Penggunaan Material Bekas Pada Bangunan - lumbangaol, partahi; Sidabutar, Ros Anita; Simanjuntak, Salomo; Sinaga, Andre Damara (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2023)
This study aims to find out the reasons that encourage the reuse of used materials in buildings. The data collection method was carried out by means of a questionnaire survey and interviews with respondents involved in the use of used materials, especially used wood. Respondents consist of used material traders, used material users, building contractors, foremen and building construction contractors who are used material producers. The research was carried out at used building material sales centers in Medan City, which are usually located on Jalan Pahlawan, Medan Perjuangan District, Jalan BrigJen Katamso, Jalan Gagak Hitam, and Jalan Helvetia Raya. Overall there were 10 respondents who participated. This study concludes that the main reason for using used wood materials is related to the price difference between used materials and new materials. Even though the use of used goods has a positive impact on efforts to preserve the environment, environmental conservation considerations have not become an important consideration in the use of used materials in the city of Medan.